An appraisal of usage and satisfaction of digital resources in academic libraries : a case study at University of Malaya - Haniza Adnan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2013)
The aim of this study was to measure the level satisfaction and usage of the UM Library digital resources. A survey method was employed to conduct a research. Using non-probability sampling method, three faculties (Art and Social Science, Science and Computer Science and Information Technology) from University of Malaya were selected as the sample of this study. The total population of postgraduate students for these faculties was very large, therefore, a sample size of 340 out of 2600 were taken to represent the total. A structured questionnaire using a five point likert scale was used to measure the satisfaction level of respondent. Findings clearly revealed that more than 72% of postgraduate students had used digital resources for their research works. However, the frequency of usage was low. The findings from the study show that the majority (80%) of respondents were satisfied with the digital resources offered by the UM Library. In addition, the study also found some of the respondents faced problems while using digital resources. The results also concluded that there are no significant differences between gender, faculty and usage of UM Library digital resources.